2012
DOI: 10.1093/intqhc/mzr080
|View full text |Cite
|
Sign up to set email alerts
|

Changes in clients' care ratings after HIV prevention training of hospital workers in Malawi

Abstract: HIV prevention training for health workers can have positive effects on clients' ratings of services, including HIV-related confidentiality and teaching, and should be scaled-up throughout Malawi and in other similar countries. Hospitals need to improve laboratory and pharmacy services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Patient satisfaction is increasingly recognized as an essential component of evaluating health systems in developing countries [26]. While a few studies have found significant effects of health interventions in Africa on improving patient satisfaction [27][28][29][30], patient satisfaction is still infrequently measured in assessing the success of health interventions in resource-limited settings. This study demonstrates both the feasibility and utility of measuring patient satisfaction as a critical component of QI initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction is increasingly recognized as an essential component of evaluating health systems in developing countries [26]. While a few studies have found significant effects of health interventions in Africa on improving patient satisfaction [27][28][29][30], patient satisfaction is still infrequently measured in assessing the success of health interventions in resource-limited settings. This study demonstrates both the feasibility and utility of measuring patient satisfaction as a critical component of QI initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…In Malawi, patients rated HIV prevention services more positively after the hospital workers (including physicians) received training in delivering peer-led HIV prevention interventions. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Komponen proses terutama pada penanganan pasien yang bisa terkendala seperti alat yang kurang memadai, tempat tunggu yang kurang nyaman, tidak kondusifnya lingkungan rumah sakit dapat berakibat pada penilaian pasien terhadap layanan kesehatan, yang dapat mempengaruhi kunjungan selanjutnya (Milella et al, 2021). Hal ini juga didukung dalam penelitian bahwa proses berpengaruh signifikan terhadap kepuasan pelanggan (Chimwaza et al, 2012) Elemen kelima people, Rumah Sakit salah satu faktor penting adalah Sumber Daya Manusia yang juga berperan penting dalam suksesnya Rumah sakit tersebut (Williams et al, 2013). Kepuasan pasien sangat dipengaruhi oleh penyedia layanan sehingga manajemen Rumah sakit akan mempertimbangkan untuk merekrut tenaga medis dan administrasi yang sesuai dengan jabatannya, selain kemampuan hardskill juga diperlukan kemampuan soft skill seperti keramahan, kesungguhan dalam melayani, komunikasi yang baik dan sopan yang semua itu bertujuan untuk meningkatkan kepuasan pasien sehingga mempengaruhi pilihan dalam kunjungan rumah sakit Kembali (Bao et al, 2013).…”
Section: Pembahasanunclassified